INTERPRETATION IN TRANSLATION SEBAGAI PENDUKUNG KUALITAS TERJEMAHAN DISCURSIVE CREATION UNTUK MEMINIMALISIR KESALAHDUGAAN KONTEKS JUDUL BUKU - Mochamad Nuruz Zaman (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Many book stores display the legalized-closed book. Besides people do not understand about English book, they will fell confuse and difficult to know the short content, they tend to ignore it to choose the Indonesia book. That problems needs the alternative solution for the readers and moviegoers to minimize alleged context in book title. Researchers conduct the alternative of supporting quality in discursive creation technique that relays the equivalences the content box consideration, namely interpretation in translation. It is presented as the secondary or alternative in translation quality. Combining the comprehensive interpretations and translation aspects. The research is translation level on embedded research by applying descriptive qualitative approach. Data sources contain of documents and informants. Purposive sampling used to accommodate the whole data gotten in research location. Triangulation techniques were data sources and methods triangulation design. Assessment results of accuracy were 13 data (52%) accurate and 12 data (48%) less accurate. Assessment results of acceptable were 22 data (88%) acceptable and 3 data (12%) less acceptable. Thus, interpretation in translations is able to be applied as the translations quality alternative in discursive creation technique to minimize the alleged context of the book titleKeywords: book title, discursive creation, translation quality